Comparison between self-gripping, semi re-absorbable meshes with polyethylene meshes in Lichtenstein, tension-free hernia repair: preliminary results from a single center - Percalli, Luigi; Pricolo, Renato; Passalia, Luigi; Riccò, Matteo (Acta Biomedica Atenei Parmensis, 2018)
Even tough inguinal hernia repair is among the commonest operations in general surgery, the choice for an optimal approach continues to be a controversial topic. Because of the low recurrence rates and low prevalence of complications, tension-free mesh augmented operation has become the standard technique in inguinal hernia surgery, significantly reducing hernia recurrence rates. On the contrary, prevalence of chronic postoperative groin pain (CPGI) i.e. pain beyond a three month-postoperative period still remains significant: as rates of CPGI may range between 15% and 53%, surgical approaches aimed to avoid chronic post-hernioplasty pain have been extensively debated, and the avoidance of CPGI has become one of the primary endpoints of surgical research on inguinal hernia repair). Recently, a sound base of evidence suggested that the entrapment of peripheral nervous fibers innervating part of the structures in the inguinal canal and stemming from ilioinguinal (Th12), iliohypogastric (L1) nerves as well as from the genital branch of the genito-femoral nerve (L1, L2), may eventually elicit CPGI (1-10). Consequently, innovative fixation modalities (e.g. self-gripping meshes, glue fixation, absorbable sutures), and new material types (e.g. large-pored meshes) with self-adhesive sticking or mechanical characteristics, have been developed in order to avoid penetrating fixings such as sutures, clips and tacks. However, some uncertainties still remain about the pros and cons of such meshes in terms of chronic pain, as new, innovative mesh apparently does not significantly reduce the rate of CPGI. Parietex ProGrip® (MedtronicsTM) is a bicomponent mesh comprising of monofilament polyester and a semi re-absorbable polylactic acid gripping system that allows sutureless fixation of prosthetic mesh to the posterior inguinal wall. As ProGrip® does not requires additional fixation, inguinal canal may be closed within minutes after adequate groin dissection, ultimately shortening operating time. In other words, ProGrip® has the potential for significant savings, in terms of surgical and post-operating costs as well (10). The aim of our study is therefore to compare the results of the same technique with two different mesh materials (ProGrip® mesh vs. polyethylene mesh), in terms of operative time, post-operative pain, complications, and recurrence rates.